Responses of marine benthic microalgae to elevated CO2 - Johnson, V; Brownlee, C; Rickaby, R; Graziano, M; Milazzo, M; Hall-Spencer, J (2013)
Increasing anthropogenic CO emissions to the atmosphere are causing a rise in pCO concentrations in the ocean surface and lowering pH. To predict the effects of these changes, we need to improve our understanding of the responses of marine primary producers since these drive biogeochemical cycles and profoundly affect the structure and function of benthic habitats. The effects of increasing CO levels on the colonisation of artificial substrata by microalgal assemblages (periphyton) were examined across a CO gradient off the volcanic island of Vulcano (NE Sicily). We show that periphyton communities altered significantly as CO concentrations increased. CO enrichment caused significant increases in chlorophyll a concentrations and in diatom abundance although we did not detect any changes in cyanobacteria. SEM analysis revealed major shifts in diatom assemblage composition as CO levels increased. The responses of benthic microalgae to rising anthropogenic CO emissions are likely to have significant ecological ramifications for coastal systems. © 2011 Springer-Verlag.